An Analysis of the Merdeka Curriculum on Improving Students' English Speaking Skills: Teachers and Students Perceptions at SMAN 2 Mataram - Jihad; Farmasari, Santi; Susanti, Ni Wayan Mira (Journal of English Education Forum (JEEF), 2025)
The study investigates the teachers and students’ perceptions of the merdeka curriculum on improving english speaking Skills among students' at SMAN 2 Mataram. There were eight students and two teachers involved as samples. The research data were collected through interviews and classroom observation. The Merdeka Curriculum at SMAN 2 Mataram has significantly improved students' English speaking skills through flexible learning approaches, teacher support, and active student participation in speaking activities. Data analysis was conducted in three stages: data reduction, data display, and conclusion drawing. Relevant data from observations and interviews were selected, organized, and interpreted to address the research objectives. Data show that the curriculum encourages a shift from standard teacher-centered learning to a more student-centered approach, using various teaching methods like discussions and presentations. Classroom observations support these findings, with students actively participating in speaking activities and becoming more comfortable using English in everyday situations. The curriculum's flexibility allows students to choose assignments that suit their interests and comfort levels, increasing motivation to participate. The study concludes that the Merdeka Curriculum is an ideal tool for improving English language growth in various educational contexts which also imply that English teachers have more rooms to create learning activities more flexibility.